2015
DOI: 10.1080/10106049.2014.985743
|View full text |Cite
|
Sign up to set email alerts
|

Developing a spectral library of mangrove species of Indian east coast using field spectroscopy

Abstract: Development of a spectral library is a prerequisite for the higher order classification of satellite data and hyperspectral image analysis to map any ecosystem with rich diversity. In this study, sampling methodology, collection of field and laboratory spectral signatures and post processing methodologies were investigated for developing an exclusive spectral library of mangrove species using hyperspectral spectroscopic techniques. Canopy level field spectra and leaf level laboratory spectra were collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Therefore, it is recommended that spectral smoothing be performed in order to produce a spectral signal that represents the original spectra without the interference of noise [44]. The Savitzky-Golay filter [45] is a common smoothing technique used in hyperspectral remote sensing [43,46,47]. Savitzky-Golay is based on least-squares approximation, which determines smoothing coefficients by applying a polynomial equation of a given degree and cluster size [45].…”
Section: Spectral Smoothingmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is recommended that spectral smoothing be performed in order to produce a spectral signal that represents the original spectra without the interference of noise [44]. The Savitzky-Golay filter [45] is a common smoothing technique used in hyperspectral remote sensing [43,46,47]. Savitzky-Golay is based on least-squares approximation, which determines smoothing coefficients by applying a polynomial equation of a given degree and cluster size [45].…”
Section: Spectral Smoothingmentioning
confidence: 99%
“…The Savitzky-Golay filter has become a popular algorithm for smoothing spectroscopic data (for example, see [43,47,60]). In this study, the filter proved adept at smoothing the hyperspectral signature without significantly altering the originality of the input data.…”
Section: Efficacy Of the Savitzky-golay Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Ramachandran et al (1998) initiated a study to discriminate mangrove species using spectro-radiometer and found similar radiance patterns in mangrove species with different intensity levels. As advancement, Prasad et al (2015) developed spectral library of mangrove species using field and lab spectroscopy. Similar to the studies of Ramachandran et al (1998), Kathiresan (2010) and Prasad et al (2015) in the current study, we tried to map mangrove species of Pichavaram using hyperspectral satellite data and literature-derived species spectrum as ground truth information.…”
Section: Study Areamentioning
confidence: 99%
“…As advancement, Prasad et al (2015) developed spectral library of mangrove species using field and lab spectroscopy. Similar to the studies of Ramachandran et al (1998), Kathiresan (2010) and Prasad et al (2015) in the current study, we tried to map mangrove species of Pichavaram using hyperspectral satellite data and literature-derived species spectrum as ground truth information. The study is first of its kind to map mangrove species of Pichavaram ecosystems without field survey.…”
Section: Study Areamentioning
confidence: 99%